ANALISIS RASIO MODAL KERJA PADA PT. HM SAMPOERNA TBK - Anggelina Manengkey; Frendy A. O Pelleng; Dantje Keles (Universitas Sam Ratulangi, 2017)
Working capital is very important for any company, because almost allcompanies need working capital to finance the day-to-day operations of thecompany. Companies must be able to manage working capital well so thatoperational activities can run smoothly and can achieve the optimal profit asexpected by the company. This study aims to analyze and know how theworking capital adequacy ratio. This research was conducted at PT. HMSampoerna Tbk. According to Sutrisno (2009),